2020
DOI: 10.3390/genes11050554
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CFTR Mutation Spectrum in Ethnic Russian Cystic Fibrosis Patients

Abstract: The distribution and frequency of the CFTR gene mutations vary considerably between countries and ethnic groups. Russians are an East Slavic ethnic groups are native to Eastern Europe. Russians, the most numerous people of the Russian Federation (RF), make about 80% of the population. The aim is to reveal the molecular causes of CF in ethnic Russian patients as comprehensively as possible. The analysis of most common CFTR mutations utilized for CF diagnosis in multiethnic RF population accounts for about 83% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
2
19
0
3
Order By: Relevance
“…Even though the p.F508del mutation accounts for 70% of CF mutations in white patients of northern European descent, it has differing percentages in other populations [ 18 ]. In the Russian population, the p.F508del mutation accounts for 53% of mutations [ 19 ], and this is caused by the specific ethnic background of the population. Thus, screening for known CF gene mutations did not help to ameliorate such inequities in our population, but the combination of NGS with MLPA was more successful, as explained in the Results Section.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the p.F508del mutation accounts for 70% of CF mutations in white patients of northern European descent, it has differing percentages in other populations [ 18 ]. In the Russian population, the p.F508del mutation accounts for 53% of mutations [ 19 ], and this is caused by the specific ethnic background of the population. Thus, screening for known CF gene mutations did not help to ameliorate such inequities in our population, but the combination of NGS with MLPA was more successful, as explained in the Results Section.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this whole-exome study demonstrated the overrepresentation of several disease-causing variants for Mendelian disorders, such as phenylketonuria (PAH, rs5030858), Wilson's disease (ATP7B, rs76151636), factor VII deficiency (F7, rs36209567), and the kyphoscoliosis type of Ehlers-Danlos syndrome (FKBP14, rs542489955). For the Russian population, however, pathogenic variant frequencies were reported mostly for relatively small cohorts including patients and their families and targeted at specific genes and disorders, for example, familial hypercholesterolemia (Meshkov et al, 2021;Miroshnikova et al, 2021); cystic fibrosis, phenylketonuria, alpha-1 antitrypsin deficiency, and sensorineural hearing loss (Kiseleva et al, 2020;Petrova et al, 2020); cardiomyopathy (Marakhonov et al, 2019;Zaklyazminskaya et al, 2019;Kulikova et al, 2021;Shestak et al, 2021); and breast and ovarian cancer (Brovkina et al, 2018;Solodskikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The low diversity of the CFTR gene variant spectra was revealed in the ethnic groups of the North Caucasus region. The W1282X variant accounted for 88% of Karachays ( Petrova et al, 2016 ), the high proportion of 1677delTA (81.5%) and E92K (12.5%) variants in Chechens ( Petrova N. V. et al, 2019 ), and W1282X (50%) and F508del (20%) variants in Ossetians [ Petrova et al, 2020b (in Russ.)] were found.…”
Section: Introductionmentioning
confidence: 99%